Comparison of lithium sources on the electrochemical performance of LiNi0.5Mn1.5O4 cathode materials for lithium-ion batteries - Sudaryanto, Sudaryanto; Salsabila, Nadhifah; Sari, Puspita Ayu Kusuma; Fachrudin, Adinandra Caesar; Salsabila, Adinda Atalya; Nursanto, Eduardus Budi; Priyono, Slamet; Jodi, Heri; Gumelar, Muhammad Dikdik (Center of Biomass & Renewable Energy (CBIORE), 2024)
In order to fulfill the demand for high energy and capacity, an electrode with high-voltage capability, namely LiNi0.5Mn1.5O4 (LNMO) that has an operating potential of up to 4.7 V vs Li/Li+, is currently becoming popular in Li-ion battery chemistries. This research produced LNMO by using a solid-state method with only one-step synthesis route to compare its electrochemical performance with different lithium sources, including hydroxide (LNMO-LiOH), acetate (LNMO-LiAce), and carbonate (LNMO-LiCar) precursors. TGA/DSC was first performed for all three sample precursors to ensure the optimal calcination temperature, while XRD and SEM characterized the physical properties. The electrochemical measurements, including cyclic voltammetry and charge-discharge, were conducted in the half-cell configurations of LNMO//Li-metal using a standard 1 M LiPF6 electrolyte. LNMO-LiOH samples exhibited the highest purity and the smallest particle size, with values of 93.3% and 418 nm, respectively. In contrast, samples with higher impurities, such as LNMO-LiCar, mainly in the form of LixNi1-xO (LiNiO), displayed the largest particle size. The highest working voltage possessed by LNMO-LiOH samples was 4.735 V vs Li/Li+. The results showed that LNMO samples with LiNiO impurities would affect the reaction behavior that occurs at the cathode-electrolyte interface during the release of lithium-ions, resulting in high resistance at the battery operations and decreasing the specific capacity of the LNMO during discharging. The highest value, shown by LNMO-LiOH, was up to 92.75 mAh/g. On the other side, LNMO-LiCar only possessed a specific capacity of 44.57 mAh/g, indicating a significant impact of different lithium sources in the overall performances of LNMO cathode.